Narito ang puso ko (Pasig City Viva Films, 2001)
Ellen and Louie are stranged lovers whose son is accidentally shot by Tato, a son of a prominent politician. However, in their constant vigil besides their comatose son, their feelings toward each other are rekindled, hence bringing anger to Suzette, Louie's current live-in lover. Meanwhile, Ellen struggles to seek justice for her son but finds it very difficult to have Tato arrested. Suzette. on the other hand, unable to win back Louie's love, offers herself to be a witness to support Tato's innocence.
DVD
Lorna Tolentino, Nanette Medved, Gabby Concepcion, Amy Austria
Keywords: Feature films